2023
DOI: 10.1097/aud.0000000000001328
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Thresholds, Speech Recognition, and Audibility as Indicators for Modifying Intervention in Children With Hearing Aids

Abstract: Objectives: The purpose of this study was to determine if traditional audiologic measures (e.g., pure-tone average, speech recognition) and audibility-based measures predict risk for spoken language delay in children who are hard of hearing (CHH) who use hearing aids (HAs). Audibility-based measures included the Speech Intelligibility Index (SII), HA use, and auditory dosage, a measure of auditory access that weighs each child’s unaided and aided audibility by the average hours of HA use per day. The authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
0
4
2
Order By: Relevance
“…Our results appear to conflict with those of Wiseman et al (2023), who reported an association between aided SII and language composite scores for a cohort of younger children with hearing loss (4- to 8-year-olds). The authors acknowledged that this association was questionable given the variability in the data and the influence of a small proportion of the children at the lowest SII levels.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results appear to conflict with those of Wiseman et al (2023), who reported an association between aided SII and language composite scores for a cohort of younger children with hearing loss (4- to 8-year-olds). The authors acknowledged that this association was questionable given the variability in the data and the influence of a small proportion of the children at the lowest SII levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Unaided and aided SRTs and word recognition at levels near threshold could be more sensitive than at higher presentation levels to the benefit that a particular fitting formula or hearing aid feature will provide. Second, although deviations from prescriptive targets are commonly observed in the pediatric population (McCreery et al, 2015), our results and those of Wiseman et al (2023) suggest that the effect of these deviations on language development may be smaller than expected.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Aided SII is a standard clinical tool for measuring how much speech-relevant information is accessible acoustically to children with hearing loss and is a hearing aid variable known to correlate with language outcomes in children [ 49 , 50 ]. For example, recent research suggests that children with aided SII values >0.71, auditory dosage (a measure of amount of time with auditory access), and word recognition in noise, could be used to predict spoken language abilities and guide changes in intervention [ 51 ]. Given the significant effects of alpha for the aided versus unaided responses and a lack of correlation with aided SII, the findings in this study suggest that aided SII alone may be inadequate for predicting hearing aid benefit in infants, especially when aided SII values are above 0.71.…”
Section: Discussionmentioning
confidence: 99%